Religious Moderation in The Practice of Hubbul Wathan Minal Iman at The Rambu Solo' Traditional Ceremony in Lembang Rumandan Tana Toraja - Saputra, Rifa’i Teguh; Khozin, Nur; Atikoh, Nurul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The concept of Hubbul Wathan Minal Iman in Islamic Religious Education is a spirit that upholds nationalism, culture, nationhood and religion. One of the unique traditions in this country is the celebration of the ceremony for the dead, known as the Rambu Solo' ceremony. This research aims to integrate and interconnect the Hubbul Wathan Minal Iman Concept with the Rambu Solo’ Traditional Ceremony. This research uses qualitative methods with a theoretical-descriptive approach. The results of the research show that the implementation of the Rambu Solo’ ceremony for the Toraja people consists of 7 stages which are based on Aluk Todolo. Religious moderation in this research can be seen in the way the Torajan people, who are predominantly Christian, maintain harmony with Islamic teachings about nationalism and love of the homeland, as well as how the traditions that are strongly held by the community remain in line with tolerant religious principles. This article will also analyze how traditional ceremonies that have local cultural roots can become a space to strengthen religious moderation, while still recognizing the diversity of beliefs within a community.